The Role of Teachers’ Pancasila and Civic Education as Motivator in Political Education - Mega Silvia; Helmi Hasan; Sa’dulloh Muzammil (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2019)
The aim of this study was to explore the role of teachers’ Pancasila and Civic Education (PPKn) as motivator in political education. The research was conducted at State of Senior High School 1 (SMAN 1) and State of Senior of High School 10 (SMAN 10) at Padang City. This research had employed a qualitative research with comparative studies. The data were analyzed using data analysis techniques, data presentation, and concluding. The validity of the data was tested by source triangulation. The result showed that the role of Teachers’ Pancasila and Civic Education not only educating the character of the nation's generation but emphasize the role of Teachers’ Pancasila and Civic Education as motivators in political education. Where the teacher as a motivator plays a role to give encouragement, enthusiasm, and intelligence to students in understanding political education. Keywords: Pancasila and Civic Education, PPkn, Political Education